Innovativeness: A Key Factor to Support Contractors' Business Success. (2017) - Setiawan, Harijanto; Erdogan, Bilge; Ogunlana, Stephen O.
Abstract: Indonesian contractors are challenged by high levels of competition both locally and globally. In order to be successful in competition, a contractor is required to be innovative. This study aims to clarify the concept of innovativeness and to explore its implementation particularly in Indonesian contractors. Following a thorough examination of the literature on innovativeness, semi-structured interviews were carried out with top managers of contractors in Indonesia to determine the innovativeness characteristics of Indonesian contracting firms. The qualitative data were analyzed using an inductive thematic analysis method. This study found three contractor actions to support innovations: carrying out research and development, challenging staff to be innovative and supporting programs that spark innovation.